2011
DOI: 10.1371/journal.pone.0029583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3,4-Methylenedioxymethamphetamine Administration on Retinal Physiology in the Rat

Abstract: 3,4-Methylenedioxymethamphetamine (MDMA; ecstasy) is known to produce euphoric states, but may also cause adverse consequences in humans, such as hyperthermia and neurocognitive deficits. Although MDMA consumption has been associated with visual problems, the effects of this recreational drug in retinal physiology have not been addressed hitherto. In this work, we evaluated the effect of a single MDMA administration in the rat electroretinogram (ERG). Wistar rats were administered MDMA (15 mg/kg) or saline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The flicker 1st ( Figure 2 D) and 2nd ( Figure 2 E) harmonic responses, which are thought to be the most representative of the original waveform [ 24 ], were also analyzed to assess the function of cones. The ADHD model presented a significant increase in the 1st (12.7 ± 1.5 µV) and 2nd (9.9 ± 1.1 µV) harmonic amplitude in comparison with the controls (9.4 ± 1.1 and 5.7 ± 0.5 µV, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flicker 1st ( Figure 2 D) and 2nd ( Figure 2 E) harmonic responses, which are thought to be the most representative of the original waveform [ 24 ], were also analyzed to assess the function of cones. The ADHD model presented a significant increase in the 1st (12.7 ± 1.5 µV) and 2nd (9.9 ± 1.1 µV) harmonic amplitude in comparison with the controls (9.4 ± 1.1 and 5.7 ± 0.5 µV, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…ERG recordings were performed after overnight dark adaptation to evaluate retinal physiology using corneal gold wire electrodes as previously described by our group [ 24 , 25 ]. Under dim red light (λ > 600 nm), animals were anesthetized by an intraperitoneal injection with ketamine (90 mg/kg; Nimatek, Dechra, Northwich, UK) and xylazine (10 mg/kg; Sedaxylan, Dechra, Northwich, UK).…”
Section: Methodsmentioning
confidence: 99%
“…One of the few reports available, on human, reported that retinal nerve fibre layer (RNFL) thinning was associated with chronic alcohol and tobacco use [20]. MDMA was also reported to have influence on retina physiology in rats [21]. Another research during which experimental mice were administered nicotine reported that nicotine altered retinal pigment epithelial cells morphology and function, caused thinning of the outer nuclear layer and a damaged photoreceptor-RPE interface in manners that pointed to possible pathological effects of nicotine on retina [22] Furthermore, there are reports that associated relative thinning of the retina with the chronic use of certain drugs including the hydroxychloroquine therapy in human subjects [23].…”
Section: Legendmentioning
confidence: 99%